Development of electronic worksheets based on project-based learning assisted by a virtual laboratory to train students' critical thinking skills - Dwi Wilujeng Fattikasari; Harun Nasrudin (Jurnal Pijar Mipa, 2023)
This research aims to explain the validity, practicality, and efficacy of electronic worksheets based on Project Based Learning assisted by a virtual laboratory to train students' critical thinking skills on the sub-material of factors that affect the reaction rate. The 4D development model (Define, Design, Develop, Disseminate) is used, limited to the development stage. The results of electronic worksheets validation on content validity and construct validity obtained a score with a mode of 5 for the four electronic worksheets, so the electronic worksheets developed were categorized as very valid. In the electronic worksheets practicality test on student activity observation outcomes, the relevant activity outcomes were 93.89% for meeting 1, 94.44% for meeting 2, 92.22% for meeting 3, and 93,33% for meeting 4. According to the learner response questionnaire results, the share was 91.24%, and the developed electronic worksheets were classified as very practical. The electronic worksheets efficacy test on the pretest and posttest results found that the classical completeness was 0% but increased to 83.33% in the posttest. The Wilcoxon test results showed a significant difference between the pretest and posttest scores, confirming his acquisition of an N-Gain score in the high category, so the developed electronic worksheets met the efficacy criteria.